Perspectives on Structural, Physiological, Cellular, and Molecular Responses to Desiccation in Resurrection Plants - Yathisha Neeragunda Shivaraj; Plancot Barbara; Bruno Gugi; Maïté Vicré-Gibouin; Azeddine Driouich; Sharatchandra Ramasandra Govind; Akash Devaraja; Yogendra Kambalagere (Scientifica)
Resurrection plants possess a unique ability to counteract desiccation stress. Desiccation tolerance (DT) is a very complex multigenic and multifactorial process comprising a combination of physiological, morphological, cellular, genomic, transcriptomic, proteomic, and metabolic processes. Modification in the sugar composition of the hemicellulosic fraction of the cell wall is detected during dehydration. An important change is a decrease of glucose in the hemicellulosic fraction during dehydration that can reflect a modification of the xyloglucan structure. The expansins might also be involved in cell wall flexibility during drying and disrupt hydrogen bonds between polymers during rehydration of the cell wall. Cleavages by xyloglucan-modifying enzymes release the tightly bound xyloglucan-cellulose network, thus increasing cell wall flexibility required for cell wall folding upon desiccation. Changes in hydroxyproline-rich glycoproteins (HRGPs) such as arabinogalactan proteins (AGPs) are also observed during desiccation and rehydration processes. It has also been observed that significant alterations in the process of photosynthesis and photosystem (PS) II activity along with changes in the antioxidant enzyme system also increased the cell wall and membrane fluidity resulting in DT. Similarly, recent data show a major role of ABA, LEA proteins, and small regulatory RNA in regulating DT responses. Current progress in “-omic” technologies has enabled quantitative monitoring of the plethora of biological molecules in a high throughput routine, making it possible to compare their levels between desiccation-sensitive and DT species. In this review, we present a comprehensive overview of structural, physiological, cellular, molecular, and global responses involved in desiccation tolerance.